Komunikasi Publik Pemprov NTT Terkait Kenaikan Tiket - Felisianus Novandri Rahmat; Yohanes Yerius Lando (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
This study aims to evaluate public communications made by the East Nusa Tenggara (NTT) provincial government (Pemprov) regarding the increase in the entrance fee for the Komodo National Park (TNK) area. As is known, the decision caused polemic in the community due to communication errors. The research data collection was carried out using primary data, namely conducting in-depth interviews and documentation as well as secondary data in the form of literature studies. Interviews were conducted with informants and documentation as well as secondary data in the form of literature studies. The results of the study show that the NTT Provincial Government's public communication in the future must pay attention to aspects of openness, public participation, optimizing communication media and communication skills in conveying new policies to the public.